Pretreatment of leucaena leucocephala (Petai Belalang) for fermentable sugar production - Moh, Lai Kuan (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Leucaena leucocephala (Petai Belalang) is one of the plant which rich with lignocellulosic material that consists of cellulose, hemicellulose and lignin. Lignocellulosic material is a renewable and cheaper source of sugar for biofuel production. For this project, in order to determine the reducing sugar of the plant, biomass undergoes pretreatment and enzymatic hydrolysis. Pretreatment process is use to open up the structure of lignocellulosic material of biomass; while enzymatic hydrolysis is use to cleave long chain polymer and convert cellulose substrate to reducing sugar. Seeds have been found to produce the highest yield of total reducing sugar compared to stalk and leaves after alkaline pretreatment and enzymatic hydrolysis process. The optimum condition for alkaline pretreatment was found at concentration of alkaline at 2 w/v% of NaOH, 100 of temperature with 30 minutes of residence time. The study found that 4.27 FPU of enzyme is the optimized enzyme activity for 5% substrate loading. The optimum condition for enzymatic hydrolysis to occur is when the stock solution was maintain at pH 4.8, temperature at 50 , 150 rpm and residence time at 72 hours.